Presenting a conceptual model of the effects of health tourism development on community welfare: A Grounded Theory Approach - Ali Rezapour; Forough Roodgarnejad; Nima Ranji Jifroudi (Tehran University of Medical Sciences, 2021)
Introduction: Health tourism is one of the most lucrative and competitive industries in the world and is a new field of tourism. The purpose of this study is to present a conceptual model of health tourism development on community welfare. Materials and Methods: This research is qualitatively exploratory. The study population included university professors and health tourism managers. Fifteen people participated in the study through purposive non-probabilistic sampling and through semi-structured and in-depth interviews. Data analysis was performed with MAXQDA10 software and a grounded theory approach based on three stages of open, axial and selective coding. To check the validity, two methods of participatory feedback and receiving the opinions of colleagues, and to ensure the reliability of the interviews, two methods of retesting and two coders were performed. Results: The data analysis was based on 100 keywords (open source). By identifying the relationship between the codes, 18 common concepts were categorized. The main concepts were categorized according to the axial coding method. Because traces of medical and health facilities, health tourism infrastructure, and relationship development policies were seen in most of the interviewees' quotes, they were selected as the central sub-categories of health tourism and these three items were placed at the center of the model. And other categories were associated with it. Conclusion: The development of health tourism is a tool for the development of society and increases investment in the political, social, cultural and economic sectors of society, creates employment, increases income and people's satisfaction and vitality, and promotes the development of welfare, the improvement of the quality of life and wellbeing.